Comparative 25-OH-vitamin D level in institutionalized women older than 65 years from two cities in Spain and Argentina having a similar solar radiation index - Pita Martín de Portela, María Luz (2010)
Objective: The present study evaluated and compared vitamin D nutritional status and calcium-phosphorus metabolism in institutionalized women >65 y from two cities that have a similar sun irradiation index (heliophany). Methods: The study was carried out in women living in similar social-status institutions from geographic cities having a similar solar radiation index (Lleida, Spain, n = 49, and suburban Buenos Aires, Argentina [BA], n = 48) at the end of summer. Results: Fish consumption was higher in the Lleida group, as was red-meat consumption in the BA group. In both groups mean calcium intake was 800 mg/d. The daily intake of vitamin D was higher in the BA group (P < 0.001). A total of 90% in Lleida and 86% in BA had 25-hydroxyvitamin D (25OHD) levels <20 ng/mL. A significant inverse correlation between individual 25OHD and parathyroid hormone (PTH) levels was observed in the two groups of women (r = -0.329, P = 0.035). PTH levels >100 pg/mL were found in 24% and 20% of women in Lleida and BA, respectively. There was a marked increase in carboxy-terminal telopeptide cross-links of type I collagen levels and a decrease in 25OHD with an increase in PTH levels (P < 0.05). Conversely, bone alkaline phosphatase increased significantly only when the PTH concentration duplicated the reference range. Conclusion: Even at the end of summer, vitamin D deficiency/insufficiency was prevalent in the two studied institutionalized elderly women. In the narrow range of the dietary calcium intake (close to 800 mg/d) of both studied groups, secondary hyperparathyroidism was absent when 25OHD levels were >17 ng/dL, indicating changes in the regulation control of serum PTH and consequently the changes in this threshold. As a result, vitamin D deficiency must be reversed to avoid the increment in bone turnover and to ensure the endocrine and paracrine functions of vitamin D for overall health and well-being.